DYNAMIC TENSILE TEST AND DATA VERIFICATION METHOD OF AUTOMOTIVE HIGH STRENGTH STEEL PLATE - PAN YuanAn; CAO GuangXiang; FENG YuTao; GAO WenQiang; LI Xin (Jixie qiangdu)
The mechanical properties of steel plate are an obvious sensitivity of strain rate. Accurate measurement of the dynamic properties of materials plays an important role in accurately predicting the collision resistance of the car body. Based on the universal testing machine and the horizontal hydraulic driving testing system, the true stress-true strain curves were obtained at the different strain rates. At the same time, the crush test of box-shaped parts was designed to verify the accuracy of dynamic testing data. The results indicated that the measured parameters by using the true stress-true strain data of different strain rates obtained by tensile test were applied to the finite element simulation analysis in order to study the deformation morphology of high strength steel under the crushing states in the application of automotive industry. The force-displacement curve was predicted by the finite element, which is roughly the same as the curve obtained from the crushing test. Therefore, it was verified that the accuracy of the real stress-strain curve at the different strain rates. And it assists to realize the low-cost measurement of dynamic tensile parameters of high strength steel plates. In addition, it can provide the possible design basis for the car impact protection.